Optical ammonia sensors based on fluorescent aza-BODIPY dyes— a flexible toolbox - Maierhofer, Maximilian (Anal Bioanal Chem, 2020)
We present three types of optical ammonia sensors suitable for environmental, bioprocess, and reaction monitoring. A respective fluorescent BF(2)-chelated tetraarylazadipyrromethene dye (aza-BODIPYs) is physically entrapped in a polyurethane hydrogel (HydroMed D4) forming an emulsion system with vinyl-terminated polydimethylsiloxane (PDMS). The analyte-sensitive layer is covered by a hydrophobic membrane which excludes hydrophilic substances. Three different protection layers are tested, whereby the Teflon and the hydrophobic PES layers outperform a PDMS/TiO(2) layer. Response times within their dynamic range of 15 s can be achieved, whereas the PDMS/TiO(2)-covered sensor requires at least 390 s. The three sensors entail the following concentration areas: first sensor 3 μg L(−1)–3 mg L(−1) (LOD 0.23 μg L(−1)), second sensor 0.1–30 mg L(−1) (LOD 28 μg L(−1)), and third sensor 3 mg L(−1)–1 g L(−1) (LOD 0.51 mg L(−1)). Readout is performed with a commercially available phase fluorimeter combined with optical fibers. Dual-lifetime referencing (DLR) is used as referencing method and Egyptian blue acts as an inert reference material. No cross-sensitivity to pH changes can be detected. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00216-020-02891-3) contains supplementary material, which is available to authorized users.